If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 + 5x + 13 = 180 Reorder the terms: -2 + 13 + 6x + 5x = 180 Combine like terms: -2 + 13 = 11 11 + 6x + 5x = 180 Combine like terms: 6x + 5x = 11x 11 + 11x = 180 Solving 11 + 11x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 11x = 180 + -11 Combine like terms: 11 + -11 = 0 0 + 11x = 180 + -11 11x = 180 + -11 Combine like terms: 180 + -11 = 169 11x = 169 Divide each side by '11'. x = 15.36363636 Simplifying x = 15.36363636
| y=-8y | | 17/5=x/13 | | 5(y-2)=4y-1 | | y=-3x+13 | | -3x+12=7 | | 4x^2-84=-5x | | 7(5x+3)=(2x+19) | | a+2ax= | | 4y^2-4y+6x-15=0 | | 3.7x-46=1.2x+9 | | -3.5x+2.2=-25.8 | | 2x^2-5x+a=0 | | 7(5x+4)=(2x+19) | | 7(3x/1)=-1 | | 4n^2+16n+12=0 | | 5x-7=0.5(10+2x) | | 5+-5=5+-7 | | X^3+12x^2+36=0 | | 2x-4x+2=6 | | -80/3=d | | -24x+25x^2=0 | | 3x-5.2=-0.2(x-6) | | 6x^2-102x+432=0 | | -(3x-5)-(2x-6)+1=-5(x-1)-3(x+2)+3 | | -8k/-7=8 | | Y+5=-18 | | 2b-52=22 | | 6(4x+2)=2(34+2) | | (2x+5)-(x+2)= | | 3y-1=5y-9 | | 0.5x-20=-10 | | 3a+6a=45 |